Penerapan Arsitektur Venturi Pada Pembangunan Komplek Perkantoran Pusat Pemerintahan Kabupaten Cianjur - Ahmad Aguswin; Aria Wirata Nudatar (DPPM Universitas Pelita Bangsa, 2022)
Cianjur is a district in West Java Province, Indonesia. The capital city is located in the Cianjur district. Cianjur has a district form of government led by a regent and his staff and agencies. There are several duties and obligations of the government, one of which is to provide equitable public services for the community, but what has happened in Cianjur is the lack of distribution of public services, especially for residents of South Cianjur, because of the distance from the current government office location. Based on the problems that occurred, there are several objectives of the construction of this office complex, the first aims to provide equitable public services for all residents of Cianjur, with the relocation of the Cianjur government office to the Campaka District making the location quite strategic and easy to reach because it is in the middle Cianjur Regency. Another goal is to unite all Cianjur offices in the same office complex, so that people who want to take care of their interests can be more effective because they don't have to move from office to office. In the construction of this office complex, using architectural concepts that highlight the traditional values and culture of Cianjur with the theme Venturi Architecture. Venturi architecture itself is an architectural concept that emphasizes traditional and cultural values. After going through a maximum planning process with the concept of Venturi Architecture, we got an office design that is closely related to the traditional values and culture of Cianjur. Keywords : Cianjur Regency, Office Complex, Government, Venturi Architectur